On crashworthiness design of double conical structures under oblique load. (2018) - Zhang, Yong; Wang, Jin; Chen, Tengteng; Lu, Minghao; Jiang, Feng
A novel multi-cell tube with non-collinear outer and inner conical angles (MBCT) is proposed to enhance structural performance under different load conditions. The finite element models (FEMs) are developed and validated by experimental tests. The comparative analysis is carried out to investigate the crashworthiness of different conical structures. The results indicate that MBCT has the most desirable load characteristics and highest energy absorption capacity. Furthermore, parametric studies reveal that large outer conical angle facilitates energy absorption and desirable load characteristics. Large wall thickness, on the other hand, has conflicting effects on crashworthiness since it increases peak crushing force (PCF) but cannot improve special energy absorption (SEA). Crashworthiness assessment of a MBCT crush box in a full vehicle further indicates the merits of energy absorption of double conical structures. The study offers insights on designing energy absorbers that are both weight efficient and reliable under uncertain load conditions.